1984
DOI: 10.1029/jd089id03p04927
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale analysis and forecast experiments with wind data from the Seasat A scatterometer

Abstract: A series of data assimilation experiments is performed to assess the impact of Seasat A satellite scatterometer (SASS) wind data on Goddard Laboratory for Atmospheric Sciences (GLAS) model forecasts. The SASS data are dealiased as part of an objective analysis system utilizing a three‐pass procedure. The impact of the SASS data is evaluated with and without temperature soundings from the NOAA 4 Vertical Temperature Profile Radiometer (VTPR) instrument in order to study possible redundancy between surface wind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 13 publications
(9 reference statements)
1
24
0
Order By: Relevance
“…Several studies have been made of the use of scatterometer data in weather forecast models (Cane et al 1981, Baker et al 1984, Anderson et al 1987 and in wave models (Janssen et al 1987) but all focus on the global scale. Generally, it is found that where in situ data are plentiful then the inclusion of scatterometer data has little impact but noticeable improvements occur in the data-sparse southern hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been made of the use of scatterometer data in weather forecast models (Cane et al 1981, Baker et al 1984, Anderson et al 1987 and in wave models (Janssen et al 1987) but all focus on the global scale. Generally, it is found that where in situ data are plentiful then the inclusion of scatterometer data has little impact but noticeable improvements occur in the data-sparse southern hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Baker et al (1984) show less of a quantifiable advantage due to the inclusion of SASS data in the forecast surface pressure and tropospheric wind fields than do those of Cane et al (1981), but in both studies the benefit was greatest in the Southern Hemisphere where conventional data are very sparse. Duffy et al (1984) compare 72 hour forecasts, from the U.S. Navy forecast model, derived with and without SEASAT scatterometer data.…”
Section: Simulation Studies On the Inclusion Of Wind Scatterometer Damentioning
confidence: 69%
“…It is contended that a study along these lines is a necessary follow-on to the reported work of Cane et al (1981), Baker et al (1984 and Duffy et al (1984), in readiness for evaluating the actual ERS-I-and N-ROSS-derived winds in the operational weather forecasting process. It should be noted that the problem of aliasing of wind direction will be less in the ERS-I and N-ROSS scatterometerdata because ofthe triple antenna configurations to be used (Duchossois 1983, Sherman 1984.Also the atmospheric temperature profiles, derived from the TOYS instrumentation on the NOAA satellite, are much improved on those of the VTPR.…”
Section: Simulation Studies On the Inclusion Of Wind Scatterometer Damentioning
confidence: 98%
See 2 more Smart Citations